Exploration and isolation of cyanobacteria cultures from the soils of rice fields of the republic of Kazakhstan) (ҚазҰУ хабаршысы. Экология сериясы, 2021)
The species diversity of the microalgae of two rice fields in Kazakhstan, located on the territory of the Almaty and Kyzylorda regions with different types of landscape was studied. The objects of the study were fields located in the Almaty region, Balkhash district of the village of Birlik and the Kyzylorda region of the village of Karaultobe. In the Birlik village the soil microalgae was studied for the first time. The purpose of this work was to study the microalgae of soils that were exposed to anthropogenic impact due to the cultivation of agricultural crops in them to identify and isolate cyanobacteria cultures. The above-mentioned objects are important for agriculture, as well as economic importance for the population of these areas. Therefore, the biological assessment of the soil of these objects is the most relevant. The analysis of the algological composition of the soils of rice fields identified an extensive species diversity of cyanobacteria in the studied objects. The greatest quantitative and qualitative composition in the soils revealed cyanobacteria of such types as: unicellular, colonial and filamentous forms. The scientific importance of the research is to study the species diversity of cyanobacteria of these objects. The practical importance of research is established in the fact that the results of the conducted analyses and experiments can be used in predicting the ecological state, and can also be necessary in creating recommendations for the conservation and functioning of environmental objects. According to the results of studies on obtaining algologically pure cultures from samples taken from the soils of rice fields in Almaty and Kyzylorda regions, such algological cultures of cyanobacteria as: Oscillitoria subbreris, Oscillitoria pseudogeminate, Osillitoria geitleriana, Phormidium purpurascens.Key words: microalgae of rice fields, cyanobacteria, algologically pure cultures.